Investigation on thermocompression bonding using lead free sinterable paste and high lead solder paste for high power led packaging - Chandrakasan, G. (Asian Research Publishing Network, 2016)
Persistently growing High-power LED packaging is used in various flux applications especially microelectronics, aerospace, oil and gas as well. Thermo-compression die-attach layer is perceived to be the most critical element in highpower LED packages as the increase in operating temperature requires new materials with suitable thermo-chemical properties also with suitable melting points of next generation lead free die attachment material. In this situation, Hi-lead solder (RM218: Pb92.5Sn5Ag2.5) which known as high temperature material is widely being used in most semiconductor assembly for die attach, yet it deduces few reliability challenges like solder voids, the tilt performance and also solder splash which has been considered as major quality issue in assembly of high-power LED packages. As a solution, sintering epoxy paste (SPC073-3: Sn96.5/Ag3/Cu0.5) is being considered as a replacement due to the challenges faced by using Hilead solder paste. In this case, sintering epoxy paste demonstrating excellent electrical and thermal performance for Highpower LED packages that is known to be demanded in market. Thus, this study investigates the differential pastes sintering paste and solder paste, in order to identify best die attachment material to be used in thermo-compression bonding method. Therefore, the shear strength was resulting good indication where the sintering paste was recorded 2.4 Kg/mm meanwhile the solder paste was recorded 0Kg/mm at peak temperature of 260Â°C. Besides of that, the pot life seems promising as the sintering paste seems to have constant viscosity of 100Pa*s throughout the 48 hours tested while, high lead solder paste records viscosity from 100Pa*s marginally increase as the time increase which effects the inconsistency of pot life. The voids performance proves sintering epoxy paste has the same pinhole voids as its individual, but the solder paste's pinhole voids are not same as individuals which easily can fail when the particular shear force was applied. Hence, sintering epoxy paste could resolve the quality issue by using thermo-compression bonding method and produce the better reliability than the solder paste. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.